Infants Prefer Female Body Phenotypes; Infant Girls Prefer They Have an Hourglass Shape - Alexander, Gerianne M.; Hawkins, Laura B.; Wilcox, Teresa; Hirshkowitz, Amy (Frontiers in Psychology, 2016)
Adolescents and adults show preferences for male and female body shapes consistent with evolutionary theories of reproductive fitness and mate selection. However, when these preferences for females with narrow waists (i.e., 0.7 waist-to-hip ratio) and men with broad shoulders (i.e., mesomorphic body shape) emerge during the lifespan is largely unknown. To address this knowledge gap, eye-movements were tracked in 144 infants (3 to 18 months of age) during computer presentation of three-dimensional human figures varying in body features thought relevant for reproductive success (e.g., secondary sex characteristics, waist-to-hip ratio). When presented with pairs of figures differing in apparent sex, male and female infants looked significantly longer at the female figure compared to the male figure, a new finding that extends previous research showing preferences for female faces in infancy. When presented with same-sex figures differing in characteristics associated with mate value, male and female infants looked longer at a low mate value male (i.e., an endomorphic body type) compared to a high mate value male (i.e., a mesomorphic body type), a finding that replicates the results of previous research. In addition, the novel use of high and low mate value female figures showed a sex difference in visual attention, such that female infants looked longer at the high mate value female figure compared to the low mate female figure whereas male infants showed the opposite pattern of results. In sum, these findings suggest that infants generally do not possess preferences for adult-defined attractive male body shapes. However, infant girls’ greater attention to a female figure with an adult-preferred waist-to-hip ratio raises the possibility that evolved preferences for 0.7 waist-to-hip ratio influence girls’ later preference for toys representing females with an hourglass shape, perhaps supporting elaboration of adult social behaviors that enhance reproductive success (e.g., cooperative breeding).